Mortality and Lifetime Income : Evidence from U.S. Social Security Records - Greenlees, John (IMF Working Papers; Working Paper, 2007)
Studies of the empirical relationship between income and mortality often rely on data aggregated by geographic areas and broad population groups and do not distinguish disabled and nondisabled persons. We investigate the relationship between individual mortality and lifetime income with a large micro data base of current and former retired participants in the U. S. Social Security system. Logit models by gender and race confirm a negative relationship. Differences in age of death between low and high lifetime income are on the order of two to three years. Income-related mortality differences between blacks and whites are largest at low-income levels while gender differences appear to be large and persistent across income levels.